Probabilistic Modeling of Annual Maximum Rainfall for Intensity-Duration-Frequency Curve Construction in the Mamminasata Region, South Sulawesi Province, Indonesia - Sanusi, Wahidah; Patahuddin, Sudarmin; Sidjara, Sahlan (Journal of Multidisciplinary Applied Natural Science, 2026)
The evaluation of extreme rainfall events is crucial for the management and planning of water resources, particularly in the design of drainage systems and water storage reservoirs. Such evaluation can be carried out through the estimation of design rainfall, which is commonly represented as rainfall intensity–duration–frequency (IDF) data. The purpose of this study is not only to apply probabilistic models to annual maximum daily rainfall data but also to construct the IDF curves of rainfall in the Mamminasata region of South Sulawesi Province. This study utilizes annual maximum daily rainfall data obtained from the Water Resources, Human Settlements, Spatial Planning, and Development Office of South Sulawesi Province, as well as the Meteorology, Climatology, and Geophysics Agency (BMKG) of Indonesia. The dataset consists of observations from 8 rainfall stations in the Mamminasata region spanning 36 years, from 1989 to 2024. The methodology involves first determining the appropriate probability distribution for each rainfall station, followed by estimating rainfall intensity using the Mononobe method, and finally constructing the IDF curves based on the estimated design rainfall and rainfall intensities for different return periods. This study found that each regency or city within the Mamminasata region generally exhibits distinct rainfall probability distributions. This highlights the importance of evaluating multiple probabilistic models to appropriately characterize the variability and extremes rainfall pattern across different locations. Based on the IDF curve, the results indicate that the longer the rainfall duration, the lower the intensity. Likewise, the shorter the return period, the lower the corresponding intensity.